Interaction between sleep duration and physical activity on mortality among cancer survivors: findings from National Health and Nutrition Examination Surveys 2007–2018 - Ruyan Chen; Jianglong Han; Si Li; Haiyu Deng; Tingting Jian; Zheyu Huang; Yuxuan Wei; Zhenming Fu (Frontiers in Public Health)
BackgroundSleep duration and physical activity (PA) are critical factors influencing mortality risk. However, the interaction between sleep duration and PA with mortality risk among cancer survivors has not been well explored.MethodsThis cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 2007–2018. Multivariable Cox regression analysis and restricted cubic splines were employed to evaluate the hazard ratios (HRs) and 95% confidence intervals (CIs) of the association of sleep duration and PA with mortality risk in cancer survivors. Multiplicative and additive interaction terms were constructed to assess interaction effects.ResultsThe study included a total of 2,528 adult cancer survivors (aged≥20 years). Sleep duration exhibited a U-shaped association with all-cause and cancer-specific mortality, while demonstrating an inverted L-shaped association with cardiovascular disease (CVD) mortality. Compared to physically inactive participants, those with adequate PA had lower risks of all-cause mortality (HR = 0.542, 95% CI: 0.540–0.543), cancer mortality (HR = 0.486, 95% CI: 0.484–0.488), and CVD mortality (HR = 0.759, 95% CI: 0.755–0.763) among cancer survivors. A significant additive interaction was found between extreme sleep duration and PA on all-cause mortality risk among cancer survivors (long sleep duration: relative excess risk due to interaction (RERI) = 1.514, 95% CI: 1.504–1.525; short sleep duration: RERI = 0.725, 95% CI: 0.713–0.737).ConclusionExtreme sleep duration and lack of PA were associated with mortality risk in cancer survivors independently and jointly. Maintain appropriate sleep duration and doing regular PA may synergistically improve cancer survival among cancer survivors.